Findings on pinless screw design for rubber extrusion - Schmidt, Leon; Schöppner, Volker; Brüning, Florian (RubberCon 2025)
Keywords: extrusion; Kautschuk; Simulation

Investigation of alternative pinless screw concepts for rubber extrusion - Schmidt, Leon; Brüning, Florian (KGK - Kautschuk Gummi Kunststoffe)
Keywords: extrusion; Kautschuk

Consideration of modeled pressure dependent viscosity data in injection molding simulation - Hanselle, Felix Paul; Schöppner, Volker; Brüning, Florian (International Polymer Processing)
Keywords: Druckabhängigkeit; Rheologie; Simulation; Spritzgießen; Viskosität

Influence of pre-shearing on the rheological properties of filled rubber compounds - Kleinschmidt, Dennis; Brüning, Florian (KGK Kautschuk Gummi Kunststoffe)
Keywords: Rheologie; Viskosität; Wandgleiten

Beschreibung des Mischverhaltens von Kautschukstiftextrudern mittels simulativer und experimenteller Methoden - Kleinschmidt, Dennis (Extrusion - Grundlagen und Praxis)

Analyse des thermo-chemischen Devulkanisationsverhaltens von SBR-basierten GTR-Mischungen - Petzke, Jonas Dirk Rudolf Helmut (AZuR-Kolloquium 2025)

Improvement of injection molding simulations by application of modeled pressure dependent viscosity data - Hanselle, Felix Paul

Degradation of Polypropylene and Polypropylene Compounds on Co-Rotating Twin-Screw Extruders - Albrecht, Paul; Altepeter, Matthias; Brüning, Florian (Polymers)
The degradation of polypropylene (PP) through thermal and mechanical stress, as well as the influence of oxygen, are unavoidable when processing on a co-rotating twin-screw extruder. In previous studies, a mathematical model was developed to predict the degradation while compounding on different twin-screw extruder sizes. Additionally, the examination of filled PPs was conducted. To this end, a range of operating parameters and extruder sizes were used to process PP, and the molar mass was then determined by melt flow rate (MFR) and gel permeation chromatography (GPC) measurements to derive the degree of degradation. The model was then modified by adjusting the sensitivity parameters to allow the degradation behavior of the PPs to be described independently of extruder size. Consistent with prior research, comprehensive measurements of a PP/titanium dioxide (TiO2) compound revealed that, with a few exceptions, increasing temperatures and screw speeds and decreasing throughputs generally resulted in higher degradation. However, the application of the model to the compounds did not achieve good agreement with the measured degradation, indicating different degradation conditions due to the different thermodynamic and rheological properties of the compounds.

NUMERICAL AND EXPERIMENTAL CONSIDERATIONS OF THE CREEP OF THERMOPLASTIC FLANGE SYSTEMS FOR THE DEVELOPMENT OF AN ANALYTICAL CALCULATION METHOD - Moritzer, Elmar; Bartmann, Finn; Riedl, Alexander (Proceedings of the ASME 2025 Pressure Vessels & Piping Conference PVP2025)

Einfluss von FFF-Prozessparametern auf die elektrische Leitfähigkeit von leitfähigen TPE-Komposite - Salm, Maximilian Karl Franz; Moritzer, Elmar (Technomer 2025 29. Fachtagung)
Keywords: Additive Fertigung; Elektrische Leitfähigkeit; Compounds; TPE; Fused Filament Fabrication

Einfluss der Schichtstruktur auf die Druckfestigkeit von FDM-Bauteilen – Ein konzeptioneller Ansatz - Beutelspacher, Jonas; Scharwald, David; Moritzer, Elmar (Technomer 2025 29. Fachtagung)

Drei Spielfilme über die Wannseekonferenz als Anlass historischen Lernens - Lobner, Laura; Meyer-Hamme, Johannes; Schönhärl, Korinna (Geschichte in Wissenschaft und Unterricht)

Zum Umgang mit "Wahr-Scheinlichkeiten". Lehr- und Forschungsprojekt zur KI-gestützten Literaturarbeit - Kückmann, Marie-Ann; Schmid, Leonie (Journal für Allgemeine Didaktik JfAD Jg.13/2025 Allgemeine Didaktik und Künstliche Intelligenu (KI))
Der Beitrag präsentiert Ergebnisse eines Lehr- und Forschungsprojekts, das den studentischen Umgang mit Literatur untersucht. Konkret wurden Studierende gebeten, sich einen disziplinspezifischen Text mithilfe generativer KI zu erschließen. Gefasst als Lehr-Lernpraktik, eröffnet die Analyse der Literaturarbeit Einblicke in hochschulische Praktiken und deren Transformation. Der Zugang erweist sich als erkenntnisreich, da er einerseits die zunehmende KI-Nutzung berücksichtigt, andererseits – aufgrund der dialogischen Funktionsweise generativer KI – Einblicke in die studentische Literaturarbeit ermöglicht. Zur Untersuchung der Praktiken und deren Sinngehalt wurden Chatprotokolle in Anlehnung an konversationsanalytische Verfahren ausgewertet, um studentische Handlungsmuster zu rekonstruieren. (DIPF/Orig.)

Evaluation von Entwicklungsarbeiten zur modulübergreifenden Professionalisierung von Lehrkräften an Berufskollegs im Kontext der digitalen Transformation - Sänger, Niklas; Schmid, Leonie; Jenert, Tobias; Kremer, H.-Hugo; Kückmann, Marie-Ann

Who Bears the Costs of the UK Soft Drink Tax? An Empirical Study of Medium-Term Effects - Wiredu, Laura (Junior Management Science)

Impact of non-rotationally symmetric joint orientation on neighbouring joints and component performance in lap shear specimens - Devulapally, Deekshith Reddy; Steinfelder, Christian; Tröster, Thomas; Brosius, Alexander (MATEC Web of Conferences)
This paper discusses the influence of joint orientation with non-rotationally symmetric geometry, on load distribution and structural behavior. The focus is on understanding how changes in the alignment of individual joints affect the distribution of load, neighboring joints, and the overall performance of the component. Lap shear specimens with multiple joints arranged in a line are analyzed to explore these effects. Simplified models are used to model the joints in finite element simulations, allowing for efficient yet accurate analysis of the load distribution and structural response under varying joint orientations. Variations in joint orientation result in measurable changes in the distribution of forces on adjacent joints, influencing their behavior and that of the overall assembly. Experimental validation confirms the numerical results, providing deeper insights into the interaction between individual joints and their surroundings. This work contributes to the development of systematic approaches for optimizing the design of components with non-rotationally symmetric joints. The study highlights the importance of considering directional properties of joints in designing structural components.

Methodische Auswahl hochfester Mehrphasenstähle bezüglich ihrer lokalen und globalen Duktilität - Tröster, Thomas; Marten, Thorsten; Luig, Simon

Localized Ultrasonic Cleaning for Injection Mold Cavities: A Scalable In Situ Process with Surface Quality Monitoring - Chalicheemalapalli Jayasankar, Deviprasad; Tröster, Thomas; Marten, Thorsten (Technologies)
As global industries seek to reduce energy consumption and lower CO2 emissions, the need for sustainable, efficient maintenance processes in manufacturing has become increasingly important. Traditional mold cleaning methods often require complete tool disassembly, extended downtime, and heavy use of solvents, resulting in high energy costs and environmental impact. This study presents a novel localized ultrasonic cleaning process for injection molding tools that enables targeted, in situ cleaning of mold cavities without removing the tool from the press. A precisely positioned ultrasonic transducer delivers cleaning energy directly to contaminated areas, eliminating the need for complete mold removal. Multiple cleaning agents, including alkaline and organic acid solutions, were evaluated for their effectiveness in combination with ultrasonic excitation. Surface roughness measurements were used to assess cleaning performance over repeated contamination and cleaning cycles. Although initial tests were performed manually in the lab, results indicate that the method can be scaled up and automated effectively. This process offers a promising path toward energy-efficient, low-emission tool maintenance across a wide range of injection molding applications.

Intrinsic production of metal-carbon fiber reinforced plastic hybrid shafts using vacuum-assisted resin transfer molding - Chalicheemalapalli Jayasankar, Deviprasad; Tröster, Thomas; Ellouz, Manel; Kordisch, Thomas (Journal of Composite Materials)
Over the past decades, the importance of lightweight structures in the aircraft and automotive industries has steadily increased due to regulations aimed at reducing global warming. Work hardened steel alloys are commonly used for lightweight applications, but they face stability issues when the material thickness reaches certain thresholds. Fiber Reinforced Plastics (FRP) offer a viable alternative due to their high strength-to-weight ratio, but they are often expensive due to long production cycles and high material costs. A feasible solution lies in hybrid lightweight designs that utilize expensive FRP materials only in highly stressed areas, achieving a balance between low mass and acceptable cost. These hybrid structures are lighter than metal components and more cost-effective compared to fully FRP structures, without compromising mechanical properties. This study focuses on producing rotationally symmetrical hybrid structures using Resin Transfer Molding (RTM) combined with vacuum assistance in a single-stage process. The research examines the effects of injection pressure, mold temperature, and the interface between metal and FRP. The mechanical characterization of these hybrid structures was conducted to assess their performance under torsion, compression, and interlaminar shear strength (ILSS) loading conditions. The results indicate that hybrid designs can offer a lightweight alternative without compromising mechanical properties.

Zeros and exponential profiles of polynomials II: Examples
In [Jalowy, Kabluchko, Marynych, arXiv:2504.11593v1, 2025], the authors discuss a user-friendly approach to determine the limiting empirical zero distribution of a sequence of real-rooted polynomials, as the degree goes to $∞$. In this note, we aim to apply it to a vast range of examples of polynomials providing a unifying source for limiting empirical zero distributions. We cover Touchard, Fubini, Eulerian, Narayana and little $q$-Laguerre polynomials as well as hypergeometric polynomials including the classical Hermite, Laguerre and Jacobi polynomials. We construct polynomials whose empirical zero distributions converge to the free multiplicative normal and Poisson distributions. Furthermore, we study polynomials generated by some differential operators. As one inverse result, we derive coefficient asymptotics of the characteristic polynomial of random covariance matrices.